Advantages of titanium xerogel over titanium tetrachloride and polytitanium tetrachloride in coagulation: A mechanism analysis. (1st April 2018) - Wang, Xiaomeng; Gan, Yonghai; Guo, Shang; Ma, Xueyan; Xu, Mengshan; Zhang, Shujuan
Abstract: Titanium xerogel coagulant (TXC) worked better than titanium tetrachloride (TC) and polytitanium chloride (PTC) in a wider pH/dose range for the removal of turbidity. However, the underlying mechanisms were not comprehensively understood. In this work, the better coagulation performance of TXC than TC and PTC was systematically elucidated from the following aspects: the physicochemical properties of the three coagulants, the removal of turbidity and organic matter, and the complexation reactions in coagulation. The results demonstrate that the merits of TXC were attributable to the following characteristics: (1) the higher surface charge density/total surface site concentration/isoelectric point of TXC hydrolysates, (2) the formation of TXC hydrolysates with a net-work structure, and (3) the strong binding affinity of TXC hydrolysates to organic matter caused by the bonded acetylacetone in the TXC framework. In short, the hydrolysis behavior of TXC significantly differed from both its precursor, TC, and the prehydrolyzed PTC. The difference in the hydrolysis of TXC was derived from the gelation process, which led to the polymerization of Ti in a way different from prehydrolyzation. The elucidation of the hydrolysis mechanisms is useful for the better application of Ti-based coagulants and may shed light on the preparation of other metal salts. Graphical abstract: Image 1 Highlights: Mechanisms for the merits of TXC in coagulation was systematically elucidated. Physicochemical properties of the hydrolysates were analyzed to reveal the mechanism. The good coagulation performance of TXC was attributable to the anchored AcAc. The AcAc in TXC controlled the hydrolysis to favorably form a large net-work structure. The anchored AcAc was also beneficial to the strong binding affinity with organic matter.